Experimental investigation on effect of surface strengthening process and roughness on water droplet erosion behavior in turbomachinery. (January 2021) - Di, Juan; Wang, Shun-sen; Yan, Xiao-jiang; Cai, Liu-xi; Xie, Yong-hui
Abstract: In this paper, the water droplet erosion (WDE) performance of a typical martensitic blade material 17-4 PH (0Cr17Ni4Cu4Nb), surface strengthened laser cladding stellite and brazed stellite alloy is studied based on high-speed water jet test system. The WDE resistances from high to low are the brazed stellite alloy, laser cladding stellite alloy and 17-4 PH. For the same material, the greater the initial roughness of the target surface, the more severe is the WDE damage. Improving the surface finish of the target is conducive to the diversion and expansion of the liquid flow, prolonging the incubation period, and thus enhancing the WDE resistance. Graphical abstract: Image 1 Highlights: The WDE resistance from high to low: brazed stellite, laser cladding and 17-4 PH. The greater the initial surface roughness, the more serious is the WDE damage. The incubation period decreases with the increase of the impact angle and roughness. The material with higher surface finish has better anti-erodibility.